2015
DOI: 10.1186/s13071-015-1080-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in drug resistance genes dihydrofolate reductase and dihydropteroate synthase in Plasmodium falciparum in some states of India

Abstract: Background: Sulfadoxine-pyrimethamine (SP) combination drug is currently being used in India for the treatment of Plasmodium falciparum as partner drug in artemisinin-based combination therapy (ACT). Resistance to sulfadoxine and pyrimethamine in P. falciparum is linked with mutations in dihydropteroate synthase (pfdhps) and dihydrofolate reductase (pfdhfr) genes respectively. This study was undertaken to estimate the prevalence of such mutations in pfdhfr and pfdhps genes in four states of India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Malaria is still a major public health burden in many countries, and the most lethal malaria parasite is Plasmodium falciparum ( Pf ) [ 1 , 2 ]. An understanding of the gene function of Pf and the performance of pathogen genetic manipulations is essential for anti-malaria drug and malaria vaccine development.…”
Section: Resultsmentioning
confidence: 99%
“…Malaria is still a major public health burden in many countries, and the most lethal malaria parasite is Plasmodium falciparum ( Pf ) [ 1 , 2 ]. An understanding of the gene function of Pf and the performance of pathogen genetic manipulations is essential for anti-malaria drug and malaria vaccine development.…”
Section: Resultsmentioning
confidence: 99%
“…2001 who also reported that the N86Y mutation modulates a higher level of CQ resistance when present with the mutant K76T pfcrt genotype 34 . Mutations in the pfdhfr and pfdhps genes are associated with SP resistance and have been reported in most parts of the country 25 , 26 , 35 38 . In this study, a high level (78%) of the pfdhfr mutation (A 16 N 51 R 59 S 108 I 164, A 16 N 51 C 59 N 108 I 164, A 16 N 51 R 59 N 108 I 164 ) and a low level (6%) of pfdhps mutations (S 436 G 437 K 540 A 581 A 613, A 436 G 437 E 540 A 581 A 613 ) was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…DNA isolation from the dried blood spots was conducted according to the manufacturer’s protocol (EURx GeneMATRIX Bio-Trace DNA Purification Kit). For amplification of Pfdhfr and Pfdhps genes, nested PCR assay was performed as described elsewhere [ 7 ]. Briefly, Pfdhfr gene was amplified by using the primers AMP-1 F and AMP-2R, which was followed by the nested reaction with primers M1 and M5.…”
Section: Methodsmentioning
confidence: 99%
“…The 728-bp fragment of the second amplicon covered the codons, which are related with resistance to sulfadoxine. Finally, the purified PCR products were sequenced in both strands and the single nucleotide polymorphisms (SNPs) were analysed [ 7 ]. The sequences of Pfdhfr and Pfdhps genes were submitted to GenBank under the accession numbers MG254624–MG254671 and MG254672–MG254719, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation